Ḥa̤zrat Ṣūfī Munīrī ke nas̲rī kārnāme - Abdālī, Muḥammad ̤Tayyib (Kitāb Manzil ; milne ke pate, Shuʻbah-yi Urdū, Magadh Yūnīvarsiṭī, 1977)
On the life and works of the Sufi Urdu author Sayyid Shāh Farzand ʻAlī Ṣūfī, 1838-1900.